2012
DOI: 10.1002/ceat.201100527
|View full text |Cite
|
Sign up to set email alerts
|

pH and Particle Structure Effects on Silica Removal by Coagulation

Abstract: 13Coagulation is presented as an efficient alternative to reduce the silica content in 14 effluents from recovered-paper mills that are intended to be recycled by a final reverse-15 osmosis (RO) step. Coagulation pretreatment by several polyaluminum chlorides 16 (PACls) or FeCl 3 was optimized prior to the RO process. PACls with low alumina 17 content and high basicity achieved almost a 100% removal of silica at pH 10.5. A good 18 reduction of the silica content was attained without regulating the pH by adding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…This fact can be explained by the competition between silica and the organic matter (mainly anionic) for the neutralizing capacity of the coagulant. This reverse relationship has also been described by D. Hermosilla et al (2012) [10]. Higher dosages of the coagulants were always more efficient in COD removal, however, the effect of high dosages on COD removal was more evident at pH 8.3 and 9.5, while at pH 10.5 it was less significant.…”
Section: -Results and Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This fact can be explained by the competition between silica and the organic matter (mainly anionic) for the neutralizing capacity of the coagulant. This reverse relationship has also been described by D. Hermosilla et al (2012) [10]. Higher dosages of the coagulants were always more efficient in COD removal, however, the effect of high dosages on COD removal was more evident at pH 8.3 and 9.5, while at pH 10.5 it was less significant.…”
Section: -Results and Discussionsupporting
confidence: 72%
“…Previous studies have demonstrated that coagulation with aluminum salts is effective for the treatment of deinked paper mill effluents; however, the required dosages and the conductivity of the treated waters were very high [10]. Therefore, the process was neither economically nor chemically feasible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the concentration of soluble silica exceeds its solubility, it precipitates on the membrane surface alone or with other products. In the case of colloidal silica, fouling occurs due to the accumulation of the colloids formed in the bulk solution, and accumulates on the membrane surface [16,17].Although there are many silica removal techniques proposed in the literature [18], it is usually carried out during softening processes or by coagulation at high pH [2,4,5,19,20].Coagulation with aluminum-based salts is very effective at ambient temperature, but high dosages (2500-5000 mg/L) are required to achieve high removal rates and the use of hybrid coagulants which increases considerably the treatment cost [4]. On the other hand, when silica removal is carried out during softening, it is necessary to ensure that enough hardness is present in the water.…”
mentioning
confidence: 99%
“…Although there are many silica removal techniques proposed in the literature [18], it is usually carried out during softening processes or by coagulation at high pH [2,4,5,19,20].…”
mentioning
confidence: 99%